Stolen from her royal wedding - Roscoe, Pippa (Harlequin presents, 2022)
"Princess Marit's elopement isn't exactly all she'd dreamed, but at least it is on her terms. That is, until Greek billionaire Lykos Livas steals her away in her wedding gown! Enlisted by the king, Lykos must return Marit to the palace--unwed. Yet hearing about her duty-bound life painfully recalls the memories of his own hard-won freedom. He offers her a week of rebellion traveling around Europe with him. But as the chemistry between them becomes undeniable, so does the deadline for Marit's royal return!" -- Page [4] cover.